2020
DOI: 10.1080/15475441.2020.1820340
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Learning in the Visuomotor Domain and Its Relation to Grammatical Proficiency in Children with and without Developmental Language Disorder: A Conceptual Replication and Meta-Analysis

Abstract: Children with Developmental Language Disorder (DLD) have difficulties acquiring the grammatical rules of their native language. It has been proposed that children's detection of sequential statistical patterns correlates with grammatical proficiency and hence that a deficit in the detection of these regularities may underlie the difficulties with grammar observed in children with DLD. Although there is some empirical evidence supporting this claim, individual studies, both in children with and without DLD, var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 68 publications
7
32
0
Order By: Relevance
“…Again, please note that the sample is identical to the one described by Van Witteloostuijn et al (2019;, which focuses on group comparisons on statistical learning measures. Similarly, the group of TD children partly overlaps with studies examining language and statistical learning in children with DLD (Lammertink et al, 2020a(Lammertink et al, , 2020b. These previous reports thus have a different focus than this study and there is no overlap in the interpretation of the data.…”
Section: Participantsmentioning
confidence: 66%
See 2 more Smart Citations
“…Again, please note that the sample is identical to the one described by Van Witteloostuijn et al (2019;, which focuses on group comparisons on statistical learning measures. Similarly, the group of TD children partly overlaps with studies examining language and statistical learning in children with DLD (Lammertink et al, 2020a(Lammertink et al, , 2020b. These previous reports thus have a different focus than this study and there is no overlap in the interpretation of the data.…”
Section: Participantsmentioning
confidence: 66%
“…Although we are aware that the SRT task is typically considered a sequence learning or procedural learning task, the type of learning that takes place in an SRT task can also be described as statistical: it involves tracking the co-occurrences of adjacent elements (see also, e.g., Kidd, 2012). Both statistical learning measures have previously been related to grammatical performance in children and/or have demonstrated impaired learning ability in children with DLD (SRT: e.g., Clark & Lum, 2017;Kidd, 2012;Lammertink et al, 2020a; A-NADL: e.g., Iao et al, 2017;Lammertink et al, 2020b). Besides phonological memory and statistical learning measures, our regression analysis includes other potential sources of variance in grammatical performance (children's age, gender, and SES, and their scores on measures of nonverbal reasoning, vocabulary, and sustained attention).…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…There has been considerable debate regarding whether procedural memory impairment is the underlying cause of language deficits in children with SLI [ 7 – 10 , 67 ]. Procedural memory is a type of non-declarative/implicit memory [cf.…”
Section: Summary Of Results and Discussionmentioning
confidence: 99%
“…also found that children with SLI showed significant impairments in procedural learning as compared to controls regardless of task modality (e.g., visual versus auditory). Although the focus of research within the PDH theoretical framework has been the identification of procedural memory deficits in SLI and their link to morphology and syntax deficits in these children [ 8 – 10 ], the PDH also predicts deficits for some but not all aspects of lexical processing as well. Specifically, the PDH posits that because procedural memory supports the concatenation and computation of the sequential information, deficits are predicted at the lexical-phonological level which subsequently impacts spoken word recognition, lexical retrieval, and sensitivity to word frequency effects (i.e., faster processing of high-frequency versus low-frequency words) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%